PERANCANGAN UI/UX WEBSITE FURLOVE UNTUK MENGOPTIMALKAN KEMUDAHAN PEMESANAN JASA PERAWATAN HEWAN PELIHARAAN - Rani Artika Sari; Fitra Zaelani; Aisyah Nushrah Diniyyati; Sari Armiati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The UI/UX design of the FurLove website aims to optimize the ease of booking pet care services, addressing common problems such as lack of transparent information and complicated processes on the service booking platform. This study uses the Design Thinking method, including the stages of Empathize, Define, Ideate, Prototype, and Test. The Empathize stage involves distributing questionnaires to 17 respondents to identify pain points such as difficulty finding information and making reservations. In the Define stage, 10 features were tested using the KANO method to prioritize user needs. The "Login/Register" feature is categorized as Must-be, while Home, About Us, Our Services, Consultation, Booking, User Profile, Booking History, Orders, and Logout are One-dimensional. The Ideate stage produces solutions such as online booking and notification systems, visualized through user flow. The prototype was developed using Figma, including the homepage, register/login, user dashboard, services, and booking. Quantitative evaluation with the System Usability Scale (SUS) was conducted with 17 respondents. The results showed an overall average score of 71.39, placing the FurLove website in the "Good" usability category. The score breakdown shows an average Learnability Subscore of 54.17 and an average Usability Subscore of 75.69. Based on gender, male respondents gave an average Overall SUS Score of 64.17, and female respondents gave an average of 75. These scores indicate the system is easy to use, efficient, and enjoyable, although there is variation between genders. Iterative improvements based on user feedback also contributed to the optimal usability scores. This research contributes practically to the development of service platforms in Indonesia by providing a measurable, user-centered design framework.